Complete mitochondrial genome of the Trichogaster leeri (Anabantoidei: Osphronemidae). (3rd July 2016) - Chen, Xialian; Chen, Ke; Yang, Huaqiao; Qu, Qiwen; Feng, Yu; Bai, Jie
Abstract: The complete mitochondrial genome of Trichogaster leeri is determined in this study. It is 16, 454 bp in length and consists of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and a non-coding control region (D-loop). The overall base composition of the heavy-strand (H-strand) of the T. trichopterus mitochondrial genome is A: 29.18%, T: 28.07%, C: 27.20% and G: 15.55%. The total length of the 13 protein-coding genes was 11, 435 bp. Phylogenetic analysis showed that the species of Trichogaster ( T. trichopterus, T. lalius and T. leeri ) formed a monophyletic group and represented close relationship with the species of Anabantoidei. This study provides an important data set for phylogenetic and taxonomic analyses of the species of genus Trichogaster .